Kinetic Study of the Formation Process of Ni-Zr Alloys - Cen, Weifu; He, Xin (International Journal of Materials Science and Technology Studies, 2024)
In this study, Ni-Zr alloy glass is chosen as the research object, and we use the molecular dynamics method to simulate and study the microstructure evolution of Ni-Zr alloy at different temperatures. The computational analysis carried out using LAMMPS, and investigated the effect of five different cold speeds on the amorphization potential of Ni-Zr. Additionally, the structural properties of Ni-Zr amorphous clusters at different cold speeds were elucidated. The results shown that cold speed is a key factor influencing the ability of Ni-Zr to form amorphous. Furthermore, amorphous formation is more likely to occur at higher cold speeds. The formation of amorphous is facilitated under the condition of higher cold speeds. By investigating the microevolutionary process and the relationship between structural entropy and temperature, it can be seen that the entropy value of the structure shows an increasing trend with the increase of temperature and cold speed. This indicates that the structure’s instability increases with increasing cold speed, which is favorable to the glass-forming ability of Ni-Zr. The kinetic process and structural analysis facilitate an in-depth comprehension of the microstructural evolution law and evolution mechanism of the Ni-Zr alloy, thereby providing a more reliable theoretical basis for the application and optimization of this material.